Self-rated health by HIV-infected individuals undergoing antiretroviral therapy in Brazil - Paulo Roberto Borges de Souza Junior; Célia Landmann Szwarcwald; Euclides Ayres de Castilho (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
In 2008, a survey was applied to a probabilistically selected sample of 1,245 HIV-infected patients on antiretroviral therapy in Brazil. In this work, the analysis was focused on self-rated health. The analysis was conducted according to sex, age, socioeconomic variables, and clinical and treatment-related patient characteristics. Through stepwise logistic regression procedures, the main predictors of good perception of health status were established. Results showed that 65% self-rated health state as good or excellent, 81% do have no or slight difficulty in following treatment, but 34% men and 47% women reported intense or extreme degree of anxiety/worry feelings. Educational level, work situation, presence of side effects and AIDS-related symptoms were the main predictors of good self-perception of health. Problems related to animus status, involving worry and anxiety about the future are still barriers that must be overcome to improve quality of life of people living with HIV/AIDS.